2023
DOI: 10.1111/trf.17359
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID‐19 pandemic on blood donation and transfusions in the United States in 2020

Abstract: IntroductionReports have suggested the COVID‐19 pandemic resulted in blood donation shortages and adverse impacts on the blood supply. Using data from the National Blood Collection and Utilization Survey (NBCUS), we quantified the pandemic's impact on red blood cell (RBC) and apheresis platelet collections and transfusions in the United States during year 2020.MethodsThe 2021 NBCUS survey instrument was modified to include certain blood collection and utilization variables for 2020. The survey was distributed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…There were notable increases in the costs paid for most blood products between 2019 and 2021. The increases appear to be steeper than in previous years, for unclear reasons, although impacts from the COVID‐19 pandemic and observed monthly fluctuations and transient shortages in the blood supply could play a role 41 . Additionally, as the uptake for certain safety interventions increases, the cost burden on hospitals is likely to be higher, since safety interventions like treating platelets with PRT and molecular genotyping of blood donors and recipients are generally more expensive than the alternatives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were notable increases in the costs paid for most blood products between 2019 and 2021. The increases appear to be steeper than in previous years, for unclear reasons, although impacts from the COVID‐19 pandemic and observed monthly fluctuations and transient shortages in the blood supply could play a role 41 . Additionally, as the uptake for certain safety interventions increases, the cost burden on hospitals is likely to be higher, since safety interventions like treating platelets with PRT and molecular genotyping of blood donors and recipients are generally more expensive than the alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…The increases appear to be steeper than in previous years, for unclear reasons, although impacts from the COVID-19 pandemic and observed monthly fluctuations and transient shortages in the blood supply could play a role. 41 Additionally, as the uptake for certain safety interventions increases, the cost burden on hospitals is likely to be higher, since safety interventions like treating platelets with PRT and molecular genotyping of blood donors and recipients are generally more expensive than the alternatives. For example, data from the 2021 NBCUS indicate that pathogen-reduced apheresis platelets are approximately $100 more per unit, within each facility size stratum, than leukoreduced apheresis platelets (range: $70-$111).…”
Section: Costmentioning
confidence: 99%
“…A stabilization in blood collection and use is further supported by the results of the 2020 data collected in the 2021 NBCUS Supplemental sections, which were added to ascertain blood collection and use trends in the United States during the COVID-19 pandemic. 21 Data from the Supplemental sections suggest that annualized blood collection and use during 2020 were also stable. 21 The stabilization of blood collection and use seen in 2021 suggests blood supply is currently meeting demand.…”
Section: Discussionmentioning
confidence: 99%
“…21 Data from the Supplemental sections suggest that annualized blood collection and use during 2020 were also stable. 21 The stabilization of blood collection and use seen in 2021 suggests blood supply is currently meeting demand. Furthermore, it appears the recent declining trends may have been driven mostly by a decline in demand.…”
Section: Discussionmentioning
confidence: 99%
“…Poor implementation of blood component transfusion guidelines leads to over-transfusion, as the authors showed in the previous publication regarding red blood cells (RBC) [ 15 ]. Over-transfusion of PC also decreases the availability of this scarce resource, which is particularly important during pandemics when recruitment of donors is compromised, an example being the novel coronavirus disease (COVID-19) pandemic [ 16 ]. The most recent PC transfusion guidelines were published in 2015 by the Association for the Advancement of Blood and Biotherapies and in 2017 by the British Society of Hematology (BSH) [ 2 , 17 ].…”
Section: Introductionmentioning
confidence: 99%